(untitled) (Journal of Hama University, 2026)
The research aimed to identify the level of psychological stress among mothers of children with mental handicap and mothers of children with autism spectrum disorder in the city of Lattakia and what are the most common methods of coping with psychological stress among them. The researcher adopted the descriptive approach, and the research tools are the psychological stress scale prepared by Al-Saratawi and Al-Shakhs (1998) and the questionnaire of methods of coping with psychological stress prepared by the researcher. The research community consisted of all mothers of children with mental handicap and autism spectrum disorder in the city of Lattakia. The research sample consisted of (40) mothers, including (22) mothers of children with mental handicap and (18) mothers of children with autism spectrum disorder who visit the Women’s Support and Empowerment Center in the city of Lattakia. They were drawn using a simple random method. The results indicated a high level of psychological stress among Mothers of children with mental handicap and the presence of a low level of psychological stress in mothers of children with autism spectrum disorder. It was also found that the most common coping style in mothers of children with mental handicap is the avoidance style; while the planning style was the most common style in mothers of children with autism spectrum disorder.